Family Income and Gang Presence in the Neighborhood: Diminished Returns of Black Families - Shervin Assari (Urban Science, 2020)
Background: Based on the Minorities’ Diminished Returns (MDRs) framework, indicators of high socioeconomic status, such as higher family income, show weaker protective effects on various developmental, behavioral, and health outcomes for Black than White families. As a result of these MDRs, Black families who access education and income still report high levels of depression, smoking, obesity, and chronic disease. Limited knowledge exists on MDRs of income on neighborhood quality. Aims: Built on the MDRs framework, this study tested the hypothesis of whether the effect of family income and maternal education at birth on neighborhood gang presence varies between Black and White families. The hypotheses were that: (1) higher income families would report lower gang presence in their neighborhood, and (2) compared to Whites, Blacks would show weaker protective effects of family income on gang presence in their neighborhood. Methods: The Fragile Families and Child Wellbeing Study is a 15-year follow up study of a random sample of births in cities with larger than 200,000 population. Two thousand nine hundred and nineteen White or Black families were included and were followed from birth of their child for 15 years. The predictors were family income and maternal education at birth, treated as categorical variables. The outcome was gang presence in the neighborhood at age 15. Logistic regression was used for data analysis. Results: Higher maternal education at birth was inversely associated with gang presence in the neighborhoods, while family income at birth did not show an effect on reducing gang presence in the neighborhood at age 15. Family income at birth and race interact, suggesting that the association between family income at birth and gang presence in the neighborhood at age 15 was weaker for Black than White families. Our race-stratified models also showed an inverse effect of family income at birth on gang presence in the neighborhood at age 15 in White but not Black families. Conclusions: Diminished returns of family income at birth on neighborhood safety and social disorder may be a mechanism that contributes to racial health disparities in higher socioeconomic status and also poor outcomes for Black families across socioeconomic status (SES) levels. That is, a smaller protective effect of family income on changing the real lives of Black compared to White families may be one of the mechanisms by which health is worse than expected in Black families, across the entire SES spectrum. The health, behavioral, and developmental disparities are not only due to the racial gap in SES but also diminishing returns of socioeconomic status indicators such as family income for racial minorities. Research should study contextual and structural factors that reduce Black families’ ability to mobilize their human capital and secure health outcomes in urban settings.